Operation of the bayt al-Māl in Saki: implications for poverty alleviation in Nigeria (2017)
Different researches have brought to the fore a number of remarkable contributions of the Bayt Al-Māl as a fiscal policy in the redistribution of wealth. In Nigeria, a few studies have been undertaken to evaluate the evolution and state of the Bayt Al-Māl. None of the studies however have undertaken an analysis of the operation and impact of the Bayt Al-Māl in the town of Saki as a mechanism for the redistribution of wealth. Therefore, this paper examines the activities and impact of Saki’s Bayt Al-Māl in meeting some of the growing needs of Muslims, including in the areas of poverty alleviation, education and health. The study reveals that Saki’s Bayt Al-Māl has recorded tremendous achievements in meeting some of the growing needs of Muslims and non- Muslims in the areas of health and education through the establishment of a Muslim School of Basic Midwifery, Muslim Medical Foundation, Muslim Hospital, and Muslim Primary and High Schools. The paper concludes that a sound Bayt Al- Māl is a necessary pre-condition for the pursuit of effective poverty alleviation measures. The paper recommends that Zakat should be one of its main sources of funding.